Normativität des Korans im Zeichen gesellschaftlichen Wandels Theologische und religionspädagogische Perspektiven - Ulfat, Fahimah; Khalfaoui, Mouez; Nekroumi, Mohammed (Theologie, Bildung, Ethik und Recht des Islam, 2022)
In a time of rapid societal changes around the globe, there is a pressing need for genuine elucidation of Muslim moral values and norms, especially in migration contexts. These rapid changes raise questions about the conservation of the 'self' and the adaptation of norms and values to real-life conditions or contexts. Muslims, confronted by the conflicting demands of tradition and modernity, often search for answers in theological normativity, particularly in conceptualisations of ethical norms and values. In this context, the legal verses in the Qurʾān, called normative verses (āyāt al-aḥkām), constitute key points of reference. Because the plurality of Islamic conceptualisations of norms requires a multidisciplinary approach, this collection of articles examines the topic from the perspective of three different disciplines of Islamic theology: Qurʾānic hermeneutics, principles of Islamic jurisprudence and religious education. With contributions by Mehmetcan Akpinar, Mouez Khalfaoui, Abdelaali El Maghraoui, Mohammed Nekroumi, Hossam Ouf, Sara Rahman, Peter Saleh Spiewok, Farid Philipp Suleiman, Said Topalovic und Fahimah Ulfat.